Validity and Reliability Study of Turkish Version of “Muscle Dysmorphic Disorder Inventory” and “Bodybuilder Image Grid” Scales - Devrim, Asli; Bilgic, Pelin (Current Nutrition & Food Science, 2019)
Background: Although bigorexia symptoms are rapidly increasing, it is mostly an underrecognized condition in Turkish male bodybuilders. There are no validated screening tools to identify the symptoms. Objective: The purpose of this study is to evaluate the validity of the Turkish version of the MDDI and the BIG towards the diagnosis of bigorexia and to provide health care professionals with early screening tools. Methods: One hundred twenty male bodybuilders, fifty-eight professional bodybuilders and sixtytwo recreational bodybuilders, all of whom matched the research criteria, were included in this study. MDDI and BIG forms were filled by the bodybuilders, along with an “Individual Characteristic Information Form”, a “Nutrition-related Information Form”, and a “Bodybuilding-related Information Form”. To evaluate the construct validity, factor analysis was conducted and resulted in a threefactor construct. Results: The factor-loading values ranged from 0.542- 0.827. Calculations of Cronbach’s alpha for the MDDI sum (α = 0.657) revealed a good internal consistency. The MDDI, BIG O, and BIG S intraclass correlation coefficients (ICC) were found to be 0.840, 0.908, and 0.879, respectively. As a result, MDDI had acceptable reliability and that of BIG O and BIG S was excellent. Discussion: Turkish MDDI, BIG-O and BIG-S forms proved to be valid and reliable scales and were adequate for determining the symptoms of bigorexia in male bodybuilders. Using these forms, there was a statistically significant relationship between bigorexia and eating disorders, which were significantly positively correlated. Conclusion: Our results support the feasibility of using the MDDI, the BIG-O, and the BIG-S forms to determine symptoms of bigorexia in Turkish population. Further studies are needed to confirm if this result can be generalized to female bodybuilders.
Keywords: muscle dysmorphia